Instructor's manual : - Smith, Lorraine C. (Thomson/Heinle, 2005)
The updated Reading for Today series features a broad range of reading materials and resources to prepare students for academic success. The core of the series consists of reading passages of general and academic internet which provide a context for vocabulary dvelopment.